APLIKASI PEMESANAN CATERING SEHAT BERBASIS WEB: STUDI KASUS OYZA FIT LIFE - Ahza Rafie Khalis; Bagus Mulyawan; Manatap Dolok Lauro (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Oyza Fit Life is a company that provides healthy catering services, focusing on nutritious food that supports a healthy lifestyle for urban communities. With increasing awareness of the importance of a balanced diet, demand for catering services like Oyza Fit Life is growing. However, the company faces significant operational challenges. The manual order process has led to various issues, including inaccurate order records and disorganized customer data management. Additionally, the lack of digital technology adoption has hindered market expansion and limited wider interaction with potential customers. This study aims to design a web-based application that addresses these challenges by offering a more efficient digital solution. The method used in this study is the Agile methodology, specifically the Scrum framework. This approach was chosen due to its flexibility, allowing the application to be developed iteratively, with sprints planned to complete specific features within a short period. Each sprint involves planning, development, testing, and evaluation, which are repeated to ensure the application’s quality and alignment with business needs. The application has simplified the customer experience by allowing them to view detailed menus, place orders according to dietary preferences, and track their orders in real time. On the business side, the application enables Oyza Fit Life to manage customer data, sales, and inventory in a more structured and easily accessible manner.